The Indexing Strategy to Prevent Worm Holes in Manet - An Analysis - Nithyapriya, J; Pazhanisamy, V (International Journal of Computer Sciences and Engineering, 2025)
A temporary network of wireless mobile hosts without the assistance of standard administration form mobile ad hoc network (MANET). It has a dynamic topology because mobiles can enter and leave the network continuously. As MANET are wireless, dynamic and have no central administration, maintaining security in this network is difficult. The wireless nature of the communication makes nodes susceptible to various kinds of attacks such as black hole attack, worm hole attacks, DoS attacks etc. In present work, we aim at detection and prevention of the wormhole attack